GERAKAN MASYARAKAT SIPIL DALAM MEMILIH KOTAK KOSONG PADA PILKADA KABUPATEN MAROS TAHUN 2024 - Haerani, Zul; Rahman, Abdul; Muh. Nato, Alhaq; La Ode, Wahiyuddin (Jurnal Governansi, 2026)
The 2024 simultaneous Regional Head Elections in several regions in Indonesia have shown interesting political phenomena, one of which is the emergence of a civil society movement to vote for the empty box. This phenomenon occurs primarily in regions with only one candidate pair, which indirectly limits democratic choices for voters. This study aims to analyze the civil society movement to vote for the empty box as an alternative form of political participation. The method used is descriptive qualitative with a phenomenological approach. Primary data were collected through in-depth interviews with 10 informants selected purposively consisting of movement activists, community leaders, and active voters, supported by participant observation and visual documentation. Secondary data were obtained from official documents of the Maros Election Commission (KPUD), mass media coverage, legal regulations, and academic literature for the 2020-2024 period. Data analysis used thematic analysis with triangulation validation. The results of the study indicate that the civil society movement supporting the empty box is a form of reflective political participation driven by dissatisfaction with public services, rejection of single candidates, and a desire for democratic alternatives. By obtaining 35% (68,527 votes) of the total valid votes, this movement put real pressure on the local political process and demonstrated active resistance by citizens to political monopoly.